Pray the gay away : the extraordinary lives of Bible belt gays - Barton, Bernadette (New York University Press, 2012)
While some areas of the United States have made tremendous progress in securing rights for gay people, Bible Belt states lag behind. Barton argues that conventions of small town life, rules which govern Southern manners, and the power wielded by Christian institutions serve as a foundation for both passive and active homophobia in the Bible Belt. She explores how conservative Christian ideology reproduces homophobic attitudes and shares how Bible Belt gays negotiate these attitudes in their daily lives.